Development of oil palm fruit bunch chopping machine for improving continuous sterilization process - Ali, Fatin Syakirah (2016)
At present, a bunch crusher is used to split the fresh fruit bunches (FFB) into small pieces prior to the continuous sterilization process. However, the bunch crusher causes a great force during the crushing process and results in severe damage to the FFB. Consequently, a lot of oil loss occurs in the oil condensate. Therefore, this study depicts the development of an FFB chopping machine to improve the continuous sterilization process. A preliminary study was conducted to determine the effects of different chopping methods of oil palm fruits on the FFA formation to predict the ample time required before the sterilization process. Besides, all the categories of the chopped fruits, which are minor damage, major damage, and chopped fruits (using knife blade), must be immediately transferred into the sterilization process less than 120 min to halt the development of FFA content. The mechanical properties of chopping the fruit bunch were obtained by using a fabricated chopping blade, which was fixed on the universal testing machine. The results were used to develop an FFB chopping machine. The FFB chopping machine was comprised of a conveyor unit; a chopping unit to chop the FFB; and a dropping unit to push the chopped fruit bunches out into a sterilizer. The chopping unit was comprised of a cross-shaped chopping blade and a v-shaped platform to hold the FFB during operation. On top of that, the performance of the machine was evaluated and upgraded to be more productive, as well as to meet the demand of the industry. Furthermore, the hydraulic and the pneumatic systems that were applied to replace the electric motor system had successfully increased the machine capacity from 0.38 ton/h to 2 ton/h, whereas the machine operating time was reduced from 106 s to 20 s. Other than that, the percentage of damaged fruits produced by the FFB chopping machine was reduced to 6.64% in comparison to that caused by the continuous sterilizer, which was 30.74%. On the other hand, the oil quality was measured by varying the holding time (0- 120 min) of the chopped fruit bunches. The FFA content and the moisture content were found to increase gradually from 0.97-2.21±0.29 % and 0.15-0.40±0.02 % respectively within the holding time. On the contrary, the contents of DOBI and carotene decreased from 3.43-0.85±0.09 and 430.40-326.08±0.77 ppm respectively due to oil oxidation and denature of carotenoids during heating. Apart from that, it was revealed that the chopped FFB could produce the highest percentage of detached fruits, which was 93.51±0.80%, at the pressure of 43.40 psi and 40 min of sterilization time. Nevertheless, the percentage of oil loss in condensate for the chopped FFB was found to be slightly increased as the pressure and the sterilization time were increased. In addition, this study was expanded to determine the effects of sterilization conditions in terms of storage time, pressure, and sterilization time of the chopped FFB on the oil quality, which focused on FFA, DOBI, and percentage of oil yield. As a result, the best condition was achieved at 0.75 min of holding time, 43.40 psi of pressure, and 40 min of sterilization time, which satisfied all the palm oil qualities. As a conclusion, throughout this study, the development of the FFB chopping machine had been proven to be a success as it was able to chop the FFB, and subsequently, enhanced the oil quality and the bunch strippability, besides reducing the percentage of oil loss in condensate.